2023
DOI: 10.1021/acsbiomaterials.3c00116
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Printed Hollow Microneedles by Digital Light Processing for the Buccal Delivery of Actives

Paraskevi Kyriaki Monou,
Eleftherios G. Andriotis,
Konstantinos Tsongas
et al.

Abstract: In the present study, two different microneedle devices were produced using digital light processing (DLP). These devices hold promise as drug delivery systems to the buccal tissue as they increase the permeability of actives with molecular weights between 600 and 4000 Da. The attached reservoirs were designed and printed along with the arrays as a whole device. Light microscopy was used to quality control the printability of the designs, confirming that the actual dimensions are in agreement with the digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Monou et al manufactured hollow microneedle devices using DLP printing technology. Through imaging studies, the researchers demonstrated the excellent printability of the material and confirmed the high fidelity of the printed objects compared to their corresponding CAD models [307]. Another study used DLS technology to develop gelatin methacryloyl microneedles containing amoxicillin.…”
Section: Materials Jetting (Mj)mentioning
confidence: 76%
“…Monou et al manufactured hollow microneedle devices using DLP printing technology. Through imaging studies, the researchers demonstrated the excellent printability of the material and confirmed the high fidelity of the printed objects compared to their corresponding CAD models [307]. Another study used DLS technology to develop gelatin methacryloyl microneedles containing amoxicillin.…”
Section: Materials Jetting (Mj)mentioning
confidence: 76%
“…Monou et al manufactured hollow microneedle devices using DLP printing technology. Through imaging studies, the researchers demonstrated the excellent printability of the material and confirmed the high fidelity of the printed objects compared to their corresponding CAD models [301]. Another study used DLS technology to develop gelatin methacryloyl microneedles containing amoxicillin.…”
Section: Materials Jetting (Mj)mentioning
confidence: 76%
“…They consist of small, needle-like structures that are less than 1 mm in length and can be made from a variety of materials, including metals, ceramics, , and polymers . This allows drugs to be delivered directly to the underlying layers of skin, where they can be absorbed and distributed throughout the body. , Recently, 3D-printed MNs have been introduced for many applications, as this process can produce different types of MNs (solid, hollow, biodegradable ) in different shapes and geometries with low cost, for transdermal or other routes of administration …”
Section: Introductionmentioning
confidence: 99%